Kontekstualisasi Strategi Bisnis Islami di Era E-Commerce : Implikasi terhadap Kewirausahaan dan Ekonomi Umat - Alisya Meitasari Wardani; Dinda Hafnita; Indi Isnandini Fajrin (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2025)
Digital technology chance in Indonesia presents both occasions and constraint for the development of Islamic economics, particularly in implementing Islamic business strategies through e-commerce. The adoption of digital technology, including Islamic fintech and halal e-commerce, has expanded market access, improved efficiency, and strengthened MSME competitiveness while adhering to sharia principles. This study employs a qualitative method using library research and the maqāshid shariah framework to examine the role of digital innovations such as fintech and blockchain in supporting Islamic entrepreneurship. The findings indicate that Islamic business strategies in the digital era have the potential to broaden international market reach, enhance transaction clarity, and reinforce compliance with sharia principles. Furthermore, digital innovation aligns with maqāshid shariah objectives, focusing on the protection of religion, life, intellect, lineage, and wealth. However, challenges remain, including low digital literacy, complex sharia regulations, and the risk of platform misuse. Therefore, cross-sector collaboration, the enhancement of digital and Islamic economic literacy, and strengthening the role of sharia e-commerce supervisory bodies are essential to build a fair and sustainable business ecosystem. With these strategic measures, digital technology integration can serve as a key instrument in strengthening the ummah’s economy, promoting financial inclusion, and positioning Indonesia as a global hub for Islamic economics.